Kebijakan grand design reformasi birokrasi 2010-2025 dalam penataan organisasi dan tata laksana - Agus suryono (Universitas Merdeka Malang, 2020)
Based on information collected empirically and normatively that the targets for the implementation of bureaucratic reform have not been achieved in the field of organization and governance at the institutional level of the bureaucracy in Malang City Government, partly due to: (a) Fatty organizational structures, overlapping both internal and external and not yet in accordance with the mandate of Perpres Number 81 of 2010 concerning the Grand Design of the National Bureaucratic Reform 2010-2025; (b) Standard Operating Procedures are convoluted so as to cause ineffective and inefficient public services. The objectives to be achieved in this study are: (1) To describe the causes of not achieving the target of implementing bureaucratic reform in the field of organizational structuring and management in Malang City Government (2) To describe and analyze and obtain efforts and models of acceleration in the implementation of bureaucratic reform in the field of organizational structuring and governance in the City Government of Malang. The method used is a qualitative approach, the location in this study is the Malang City Government especially the Law Bureau and the Malang City Organization. Sources of research data obtained through interviews and direct statements while those that are not directly indirect, can be in the form of notes, documents, manuals, and knowledge books. Data analysis in this study uses the interactive model of analysis of Miles and Huberman which was developed by Johnny Saldana (2013), which has three main components, among others: data reduction, data presentation, and drawing conclusions / verification. The results and conclusions obtained are the application of learning organizations in the framework of developing apparatus resources to improve performance in the Government of Malang City yet to be effective. This is due to several factors, including motivation and the ability of the apparatus to develop themselves is still low. The pattern of apparatus empowerment is considered not optimal. Learning infrastructure is inadequate, causing the process of getting information or knowledge to be hampered, cultural and relational learning has not been formed, collaboration and collegility have not grown well, there is no application of an award system that recognizes the achievements of organizational members, effective organizational structure structuring to accelerate the process of knowledge sharing , mental models, and shared vision. The application of learning organizations that can work well must also be strengthened by information technology systems that can support the creation of a communication flow or information flow to increase the capacity of the government apparatus.DOI: 10.26905/pjiap.v5i1.4027